2018
DOI: 10.1002/ece3.3925
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinism, and not interspecific competition, drives morphological variability in Australasian warblers (Acanthizidae)

Abstract: Interspecific competition is thought to play a key role in determining the coexistence of closely related species within adaptive radiations. Competition for ecological resources can lead to different outcomes from character displacement to, ultimately, competitive exclusion. Accordingly, divergent natural selection should disfavor those species that are the most similar to their competitor in resource use, thereby increasing morphological disparity. Here, we examined ecomorphological variability within an Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(110 reference statements)
1
2
0
Order By: Relevance
“…We then use these two inter‐ and intraspecific patterns of diversity to explore the history of the species’ diversification, in particular across their putative hybrid and contact zones. Our study expands on that of García‐Navas, Rodríguez‐Rey, Marki, and Christidis (2018;) who concluded that climate is a key predictor of morphological diversity in the family Acanthizidae to which thornbills belong.…”
Section: Introductionsupporting
confidence: 81%
“…We then use these two inter‐ and intraspecific patterns of diversity to explore the history of the species’ diversification, in particular across their putative hybrid and contact zones. Our study expands on that of García‐Navas, Rodríguez‐Rey, Marki, and Christidis (2018;) who concluded that climate is a key predictor of morphological diversity in the family Acanthizidae to which thornbills belong.…”
Section: Introductionsupporting
confidence: 81%
“…Parallel analyses should compare pairs of taxa with similar phylogenetic and ecological relatedness that co-occur broadly and do not share similar phenotypes to provide a null comparison of sympatric ecogeographic variation in systems lacking mimicry. If results are similar to those found in mimicry systems, then communities' ecomorphological evolution as a whole are likely being driven by other abiotic and biotic factors (García-Navas et al 2018).…”
Section: Expansion Of Researchmentioning
confidence: 55%
“…The morphological disparity is often used as a surrogate measure of biological diversity in the study of biological communities (Neustupa et al, 2009;Farré et al, 2013). This diversity is historically generated by ecological and evolutionary factors varying across scales of space and time producing variability among different geographical regions (Ricklefs, 2004;Witman et al, 2004;García-Navas et al, 2018). However, these morphological gaps between regions are being increasingly homogenized by human assisted translocation of species to global scale (McKinney and Lockwood, 1999), and the morpho-functional differentiation of nonindigenous species can be the key to gain a competitive advantage and develop invasive populations (Smith and Knapp, 2001;Azzurro et al, 2014;Nagelkerke et al, 2018).…”
Section: Discussionmentioning
confidence: 99%